Children in war and exile:Emotional reactions and signs of distress - Vidović, Vesna (Array, 1993)
A semistructured psychotherapeutic interview was carried out with the group of parents and children due to war in Croatia in order to obtain data on the effects of exposure to armed conflicts and loss of home.Od 252 displaced children exposed to armed conflict, parets reported various psychological symptoms and signs of distress in 163 of them.The children in the youngest group had developed more difficulties than others.Corelation between some previous and actual symptoms show that the exposure to possibly traumatic events does not necessarily produce regression and reactivation of earlier symptoms.